Ashton Park - Pura, Murray, 1954- (Pura, Murray, 1954- Danforths of Lancashire, 2013)
While William Danforth is in London during Parliamentary sessions, Lady Elizabeth visits a small Baptist church in Liverpool with her head cook, exposing Elizabeth to a less formal approach to Christian worship which she comes to enjoy.